2012
DOI: 10.1165/rcmb.2010-0284rc
|View full text |Cite
|
Sign up to set email alerts
|

Cellular FLICE-like Inhibitory Protein Deviates Myofibroblast Fas-Induced Apoptosis Toward Proliferation during Lung Fibrosis

Abstract: A prominent feature of fibrotic tissue in general and of lungs in particular is fibroblast proliferation and accumulation. In patients overcoming fibrosis, apoptosis limits this excessive cell growth. We have previously shown resistance to Fas-induced apoptosis of primary lung fibroblasts from mice with bleomycin-induced lung fibrosis, their escape from immune surveillance, and continued accumulation in spite of overexpression of the Fas death receptor. Cellular FLICE-like inhibitory protein (c-FLIP) is a regu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
71
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(75 citation statements)
references
References 74 publications
3
71
1
Order By: Relevance
“…Indeed, one recent study showed that FLIP induction prevents embryonic fibroblast apoptosis induced by TNF-a (48). Another report recently showed c-FLIP expression in the fibroblastic foci of IPF biopsies while demonstrating increased c-FLIP expression in IPF fibroblasts (49). Moreover, loss of c-FLIP increased the sensitivity of fibroblasts to apoptosis (49).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Indeed, one recent study showed that FLIP induction prevents embryonic fibroblast apoptosis induced by TNF-a (48). Another report recently showed c-FLIP expression in the fibroblastic foci of IPF biopsies while demonstrating increased c-FLIP expression in IPF fibroblasts (49). Moreover, loss of c-FLIP increased the sensitivity of fibroblasts to apoptosis (49).…”
Section: Discussionmentioning
confidence: 97%
“…Another report recently showed c-FLIP expression in the fibroblastic foci of IPF biopsies while demonstrating increased c-FLIP expression in IPF fibroblasts (49). Moreover, loss of c-FLIP increased the sensitivity of fibroblasts to apoptosis (49). In contrast, another study argued against a role for c-FLIP as a mechanism of apoptosis resistance in IPF fibroblasts by demonstrating that c-FLIP was expressed in the epithelium overlying fibroblastic foci but not in the fibroblasts themselves (46).…”
Section: Discussionmentioning
confidence: 99%
“…55,70,71 An accumulating body of literature demonstrates that lung fibroblasts and myofibroblasts in both mouse fibrosis models and IPF acquire an apoptosis-resistant phenotype. 41,48,55,59,70,71 Several mechanisms by which myofibroblasts evade apoptosis have been identified, 72 and several common mechanistic themes have emerged. First, soluble profibrotic mediators that activate myofibroblasts, such as TGF-b1, also promote resistance to apoptosis.…”
Section: Role Of Apoptosis In Removing Myofibroblastsmentioning
confidence: 99%
“…73,74 Third, endogenous inhibitors of apoptosis, such as Fas-like IL 1b-converting enzymeeinhibitory protein and X-linked inhibitor of apoptosis, are induced by soluble profibrotic mediators and expressed at increased levels in fibrotic lung fibroblasts. 48,56,59 Fourth, the composition and biomechanical properties of the ECM can modulate fibroblast resistance to apoptosis. 41,75 Fifth, epigenetic alterations, such as methylation of the Thy-1 promoter in fibroblastic foci of IPF, have been linked to resistance to apoptosis.…”
Section: Role Of Apoptosis In Removing Myofibroblastsmentioning
confidence: 99%
“…In this study, we employed western blot analysis and found that ADSCs inhibited tunica albuginea MFs activation, which was indicated by a time-dependent decrease in αSMA expression. Apoptosis induced by loss of adhesion or adhesion-mediated signalling (termed 'anoikis') is a main pathway of tunica albuginea MFs clearance (44). Although the precise mechanism of myofibroblast apoptosis in the resolution of wound healing and tissue repair are not well defined, anoikis is likely a relevant model to study apoptotic mechanisms since cell adhesion and biomechanical tension unloading appear to play important roles in this physiological (45).…”
Section: Discussionmentioning
confidence: 99%